International Capital Markets developments, prospects and policy issues - Folkerts-Landau, David; International Monetary Fund (Washington D.C. International Monetary Fund, 1995)
This report discusses how the control and management of financial risk have been strengthened by efforts in the official and private sectors in major industrial countries, and goes on to survey developments in international financial markets.
Includes bibliographical references
osc 17/8/16
Loans
Keywords: Capital Markets; International finance; Banks and banking, International; Finance